2017
DOI: 10.1089/cyber.2017.0319
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Resilience and Internet Addiction: A Multiple Mediation Model Through Peer Relationship and Depression

Abstract: Heavy use of the Internet may lead to profound academic problems in elementary students, such as poor grades, academic probation, and even expulsion from school. It is of great concern that Internet addiction problems in elementary school students have increased sharply in recent years. In this study, 58,756 elementary school students from the Henan province of China completed four questionnaires to explore the mechanisms of Internet addiction. The results showed that resilience was negatively correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 46 publications
3
50
0
2
Order By: Relevance
“…In a longitudinal study, it was demonstrated that gaming frequency at baseline predicted an increase in internalizing problems one year later [11]. The relationship between a deficit in resilience and occurrence of IGD may be mediated by relational difficulties with peers [12]. Three waves of longitudinal European studies named "Saving and Empowering Young Lives in Europe" showed that early symptoms of IGD and emotional problems were predictors of developing and IGD later [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a longitudinal study, it was demonstrated that gaming frequency at baseline predicted an increase in internalizing problems one year later [11]. The relationship between a deficit in resilience and occurrence of IGD may be mediated by relational difficulties with peers [12]. Three waves of longitudinal European studies named "Saving and Empowering Young Lives in Europe" showed that early symptoms of IGD and emotional problems were predictors of developing and IGD later [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, investigating how postsecondary students acquire Internet addiction and developing effective intervention techniques for Internet addiction are imperative. Studies have indicated that Internet addiction is a complex psychological phenomenon influenced by numerous factors, which can be divided into the following categories: external environments ( Wu, 2004 ; Chen et al, 2007 ; Wu et al, 2016 ), family environments ( Li et al, 2014 ), and peer relationships ( Zhou et al, 2017 ); psychological factors such as loneliness ( Özdemir et al, 2014 ; Sharifpoor et al, 2017 ), depression ( Fayazi and Hasani, 2017 ), negative affect and dissociation ( Musetti et al, 2018 ) and self-esteem ( Bozoglan et al, 2013 ; Farah et al, 2016 ); and physiological factors such as hormones and arousal levels ( Wang, 2006 ). Thus, investigating the relationships between some of these variables and Internet addiction is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has stipulated depression and anxiety as the psychological symptoms of addictive internet behaviors [ 20 ]. While there are findings showing the mediation model among resilience, internet addiction, and depression in children, no corresponding results in youth is available for clinical references [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that better resilience will be associated with a lower likelihood of internet addiction. Previous studies have shown that psychological resilience was negatively associated with the risk of Internet addiction in children [ 21 ] and adolescents (β=-0.030) [ 22 ]. Similar associations were found in university students [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%